Performance Maintenance Analysis Using QFD Method: A Case Study in Fabrication Company in Indonesia - Rizlan, Wardah; Purba, Humiras Hardi; Sudiyono, Sudiyono (Bina Nusantara University, 2018)
This research aimed to determine the needs and wants of production and management team to improve the machine and performance maintenance. Voice of the Customer (VOC) method was used to capture the needs and wants of production and management team. Meanwhile, the method of Quality Function Deployment (QFD) was used to translate the needs and wants of production and management to the technical requirement that should be done to improve machine and performance maintenance. Moreover, Total Productive Maintenance (TPM) was a part of technical requirement. From the result, it is known that long breakdown machine, huge inventory of spare part, and high cost of maintenance become the first of priority of maintenance team to achieve customer satisfaction. To develop the performance maintenance, the company should standardize the procedure, identify the critical spare part, reduce the time to purchase critical spare part, and increase lifetime of spare part.